1924 Ky. Acts 76 - (:unkn) unknown (My University, 1924)
Malicious Shooting, Stabbing or Poisoning; Deadly Weapon,§ 1166: Prohibited willfully or maliciously shooting at or drawing a gun on a person.
Keywords: BRANDISHING; COMMITTING CRIME W/ WEAPON